x =
or x = -
![(4)/(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/2ef7qw0k27nks1lxds61rbq54v3mvv6vjw.png)
consider the factors of the product 6 × - 4 = - 24 which sum to the coefficient of the x- term ( + 5)
the factors are + 8 and - 3 ( split the middle term using these factors
6x² - 3x + 8x - 4 = 0 ( factor by grouping )
3x(2x - 1) + 4(2x - 1 ) ( take out common factor of (2x - 1) )
= (2x - 1)(3x + 4) = 0
equate each factor to zero and solve for x
2x - 1 = 0 ⇒ x =
![(1)/(2)](https://img.qammunity.org/2019/formulas/mathematics/college/q5zg49mbtfrwobmmahi676fbgez56hhab0.png)
3x + 4 = 0 ⇒ x = -
![(4)/(3)](https://img.qammunity.org/2019/formulas/mathematics/high-school/2ef7qw0k27nks1lxds61rbq54v3mvv6vjw.png)